Penyaringan Ketahanan Plasma Nutfah Ubi Jalar terhadap Hama Lanas - Nani Zuraida; nFN Minantyorini; Dodin Koswanudin (Buletin Plasma Nutfah, 2005)
Screening of sweetpotato germplasm resistant to weevil was done in Indonesian Agricultural Biotechnology and Genetic Resources Research Institute Bank Gene Laboratory during October-November 2002. Fifty accessions of tuber root were evaluated. Three tuber roots were infested by five pairs of Cylas formicarius Fabr. for each accession with three replications. Three days after infestation (dai), the insects were move out from its container and 30 dai the resistance was scored. The results showed that only one accession Yoban (2%) resistant and nine accessions (18%) were moderately resistant, 24 accession were moderate susceptible (48%), and 16 accessions were susceptible (32%). Yoban variety has potential to be used as parent material in breeding of sweet potato for resistant to weevil.Key words: Sweetpotato, germplasm, resistant, weevil. AbstrakPenelitian dilakukan di Laboratorium Bank Gen, Balitbio pada Oktober-November 2002. Sebanyak 50 aksesi ubi jalar yang diuji/disaring ketahanannya diinfestasi dengan lima pasang serangga Cylas formicarius dalam kotak plastik tertutup kain kasa. Tiga hari kemudian serangga dikeluarkan dan setelah 30 hari infestasi diamati ketahanannya. Dari 50 aksesi diperoleh satu aksesi yang bereaksi tahan terhadap hama lanas, yaitu Yoban (2%), sembilan aksesi agak tahan (18%), 24 aksesi agak peka (48%), dan 16 aksesi peka (32%). Varietas Yoban mempunyai potensi untuk dijadikan tetua persilangan dalam perakitan varietas unggul yang tahan/toleran terhadap hama lanas.Kata kunci: Ubi jalar, plasma nutfah, ketahanan, lanas.